Quality of virtual education from the perspective of students and professors during the COVID-19 pandemic - Sara Mohammadi; Masoumeh Shohani; Leili Abedi; Saleh Arizavi; Aghil Rostami (Zanjan University of Medical Sciences and Health Services, 2022)
Background & Objective: Soon after the outbreak of COVID-19, Universities of medical sciences was forced to shift from face-to-face education toward online educational activities according to WHO recommendation to observe physical distancing. Therefore, the present study was conducted to determine the quality of virtual education classes from the perspective of students and professors at Ilam University of Medical Sciences. Materials & Methods: This cross-sectional study was conducted in five faculties of Ilam University of Medical Sciences in 2020. Thirty professors and 370 students participated in the study by convenience sampling. Data were collected using a researcher-made questionnaire based on the viewpoint of university professors and students about the quality of virtual classes. The questionnaire included 30 questions in four sections: the ability to use the educational system, feelings and attitudes towards the virtual class, learning and educational environment, interactive learning and perceived effectiveness, plus five questions addressing satisfaction with the training course. The data were analyzed using independent t-test at a significance level of P <0.05 by SPSS 22 software. Results: The mean and standard deviation (SD) score of the quality of virtual education classes from the perspective of professors and students was 48.6(16.2) and 47.9(25.9), respectively, which is considered moderate. There was a significant difference between professors' and students' viewpoints about satisfaction with virtual education classes (P= 0.004), indicating that the professors were more contented than students. Conclusion: Generally, professors and students rated the overall quality of virtual classes as moderate, and they were also relatively satisfied with the course.